Low-Level Vagus Nerve Stimulation Reverses Obstructive Sleep Apnea-Related Atrial Fibrillation by Ameliorating Sympathetic Hyperactivity and Atrial Myocyte Injury - Guo, Yankai; Xiaokereti, Jiasuoer; Meng, Qingjun; Cao, Guiqiu; Sun, Huaxin; Zhou, Xianhui; Zhang, Ling; Tang, Baopeng (Frontiers in Physiology, 2021)
Background: Previous studies have proved that low-level vagus nerve stimulation (LLVS) could suppress acute obstructive sleep apnea (OSA), which is associated with atrial fibrillation (AF). Objective: This study investigates the underlying electrophysiological, neural, and cardiomyocyte injury mechanisms on acute OSA-induced AF, examining whether LLVS can attenuate or reverse this remodeling. Methods and Results: Eighteen mongrel dogs received endotracheal intubation under general anesthesia and were randomly divided into three groups: the OSA group (simulated OSA with clamping of the trachea cannula at the end of expiration for 2min followed ventilation 8min, lasting 6h, n=6), the OSA+LLVS group (simulated OSA plus LLVS, n=6), and a control group (sham clamping the trachea cannula without stimulation, n=6). In the OSA+LLVS group, the atrial effective refractory period was significantly lengthened while the sinus node recovery time and AF duration decreased after the 4th hour, and the expression level of Cx40 and Cx43 was significantly increased compared to the OSA group. Norepinephrine, TH, and ChAT were significantly decreased in the OSA+LLVS group compared with the OSA group. Mitochondrial swelling, cardiomyocyte apoptosis, and glycogen deposition, along with a higher concentration of TNF-α, IL-6 were observed in the OSA group, and the LLVS inhibited the structural remodeling and expression of inflammatory cytokines. Conclusion: LLVS decreased the inducibility of AF partly by ameliorating sympathetic hyperactivity and atrial myocyte injury after acute OSA-induced AF.